Diagnostic test assessment on protist misconception - Defita Raharjo; Murni Ramli; Yudi Rinanto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
One of the fatal problems emerge in educational practice is misconception as it is related to the students’ understanding. Consequently, these must be detected at the beginning of learning process. This research was conducted to construct and develop the specific diagnostic test to detect the misconception in protist material. The instrument consisted of, Evidence and Proof (EP), Structure Communication Grid (SCG), and essay. The instruments were analyzed to determine the validity, reliability, discriminatory power, and difficulty levels. As many as 351 students of grade X, XI, and XII were selected as the samples. The samples selected from three Public High Schools and three Private High Schools in Klaten Regency using stratified random sampling. The results showed that 93.10% of the columnar (EP) items, 100% of the SCG items, and 100% of the essay questions were valid; in which the all instruments were reliable. Based on discriminatory power analysis, of the three instruments developed, there was more than 50% of the items were classified as fair level. Whereas, the difficulty level of the instruments were balance. In general, the instruments can be accepted and used after revisions. These diagnostic test instruments can also be developed for another topic.